Workshop Komprehensif Pencegahan Banjir Rob di Nusa Tenggara Barat - Fera Fitri Salsabila; Achmad Fajar Narotama Sarjan; Ida Ayu Oka Suwati Sideman (Unram Journal of Community Service, 2022)
Province of NTB is an area that often experiences floods, which result in moral and material losses such as death, damage to public facilities and infrastructure, material losses, outbreaks of infectious diseases, obstruction of transportation, stagnation of economic activity and leaves trauma to each of them individual. Several factors that cause flooding in NTB are high rainfall and the overflow of sea water to the mainland. This Community Empowerment aims to looking for a comprehensive solution in dealing with the problems of flooding and ROB in Nusa Tenggara Barat and to Encouraging all participants, even from the Government or general public to work together in preventing floods and ROB in Nusa Tenggara Barat. This activity was attended by 60 participants consisting of the Government, Academics, College students, Friends of SWE Affiliate NTB and SWE Affiliate NTB. The activities show that this activities afford a comprehensive solution in overcoming floods and ROB in NTB. We also hoped that the participants who attend can work together to prevent flooding and Rob in NTB